Symbolic meaning of the number 108 in culture and Buddhism of Mongolia - D. Urnokhdelger (Nomadic Civilization: Historical Research)
This article is devoted to the numerical symbols in Mongolian culture and religion (on the example of 108). Numbers have long been believed to have mystical significance in various cultures and religious traditions. One hundred and eight is an amazing number in world numerology. And Buddhism is no exception. Buddhism is the oldest religion in the world. The author studied the logic of explaining the symbolic meaning of the number 108 in the numerical code inherited from the symbolic thinking of the Mongols, and based on the literary and cultural sources of the Mongolian people, he tried to determine the importance that the ancestors of the modern Mongolians attached to this sacred number. The 108 numbers, which codify some of the teachings of the Buddhist religion, have been clarified by referring to the meanings that have been absorbed into the faith of worshiping and purifying the soul. The rights used by the Mongols could have 54, 27, 21, or 8 pieces. The number of mantras recited is determined by counting the beads. Each round is repeated 108 times. It is believed that after repeating any action 108 times, a person attains perfection. There is an oral legend in Mongolia that the person who recited mantras has “seashell teething” (“Dun shud”) on his palate, when the number of mantras counted by beads on the rosary is fully complete.